Shifts on Gut Microbiota Associated to Mediterranean Diet Adherence and Specific Dietary Intakes on General Adult Population - Garcia-Mantrana, Izaskun; Selma-Royo, Marta; Alcantara, Cristina; Collado, María C. (Frontiers in Microbiology, 2018)
There is increasing evidence for the interaction between gut microbiome, diet and health. It is known that dysbiosis is related to disease and that most of the times this imbalances in gut microbial populations can be promoted through diet. Western dietary habits, which are characterized by high intakes of calories, animal proteins, saturated fats and simple sugars have been linked with higher risk of obesity, diabetes, cancer and cardiovascular disease. However, little is known about the impact of dietary patterns, dietary components, and nutrients on gut microbiota in healthy people. The aim of our study is to determine the effect of nutrient compounds as well as adherence to a dietary pattern, as the Mediterranean diet on the gut microbiome of healthy adults. Consequently, gut microbiota composition in healthy individuals, may be used as a potential biomarker to identify nutritional habits as well as risk of disease related to these habits. Dietary information from healthy volunteers (n=27) was recorded using the Food Frequency Questionnaire (FFQ). Adherence to the Mediterranean diet was measured using the PREDIMED test. Microbiota composition and diversity were obtained by 16S rRNA gene sequencing and specific quantitative polymerase chain reaction (qPCR). Microbial metabolic activity was determined by quantification of short chain fatty acids (SCFA) on high performance liquid chromatography (HPLC). The results indicated that a higher ratio of Firmicutes–Bacteroidetes was related to lower adherence to the Mediterranean diet, and greater presence of Bacteroidetes was associated with lower animal protein intake. High consumption of animal protein, saturated fats, and sugars affected gut microbiota diversity. A significant higher presence of Christensellaceae was found in normal-weight individuals compared to those who were overweight. This was also the case in volunteers with greater adherence to the Mediterranean diet compared to those with lower adherence. Butyricimonas, Desulfovibrio, and Oscillospira genera were associated with a BMI<25 and the genus Catenibacterium with a higher PREDIMED score. Higher bifidobacterial counts, and higher total short chain fatty acids (SCFA) were related to greater consumption of plant-based nutrients, such as vegetable proteins and polysaccharides. Better adherence to the Mediterranean diet was associated with significantly higher levels of total